Inkonsistensi Ketentuan Pidana Terhadap Tujuan Kepastian Hukum Dalam Undang-Undang Republik Indonesia No 3 Tahun 2020 Tentang Penambangan Mineral dan Batubara - Christiadi Yanuar Saputro (Jurnal Hukum dan Sosial Politik, 2023)
Criminal provisions in a statutory regulation are certain doses or remedies as a means of achieving the formulated goals. The purpose of this article is to examine and analyze the inconsistency of the material content of the criminal provisions against the formulation of the objectives of legal certainty in the Law of the Republic of Indonesia No. 3 of 2020 concerning Mineral and Coal Mining. The research method uses a normative juridical method. Secondary data in the form of primary legal data on laws and regulations related to the criminal provisions of the Minerba Law is elaborated so that the adequacy of the content of the criminal provisions is able to test the clarity of the objectives of legal certainty. The results found that there were inconsistencies in criminal provisions as a means of achieving goals in the formulation of guaranteeing legal certainty. The application of Article 162 of the Mineral and Coal Law is subjective and tends to criminalize members of the community around mineral and coal mining. This fact proves that the objective of legal certainty is objective, ambiguous with subjective criminal means. The main article of criminal provisions in the Minerba Law is Article 158 which is systematically constructed with Article 35. Basically, the criminal provisions are used as the legal regime for licensing in the strategies and techniques of government control and control in the mineral and coal sector.